Fake News about health on the WhatsApp social network, during the Covid-19 pandemic, year 2022 (LACCEI, 2024)
The present investigation, which is entitled "Fake News about health in the WhatsApp social network, during the Covid-19 pandemic, year 2022", formulated the following general objective: to analyze false news about health in the WhatsApp social network , during the Covid-19 pandemic, year 2022 proposed the following methodology: qualitative approach, under the case study research design, at the level of hermeneutic scope, with a population of 20 messages and a sample of 10 messages and observation as a technique and the observation sheet as an instrument achieved the following main result: fake news cites recognized sources (government agencies and institutions, television channels, medical specialists, political representatives and scientific journals) with the aim of being credible media for readers reached the following general conclusion: fake news on the WhatsApp social network tends to produce completely false content in favor of “news”, where the authors address the issue of Covid-19 based on their personal benefits.